Association of Ultrasonography and Ultrasound-guided Fine Needle Aspiration Cytology in the Diagnosis of Thyroid Nodules - Dev, Binit; Yadav, Ajay Kumar; Taparia, Sushil; Khadka, Roshana; Walavalkar, Shripad J (Birat Journal of Health Sciences, 2021)
Introduction: Ultrasound (USG) is the most commonly used imaging method to evaluate thyroid nodules. The sonographic features of thyroid nodules are very important to determine whether the nodule is benign or malignant. Fine Needle Aspiration Cytology (FNAC) is the gold standard to determine whether the nodule is benign or malignant. Objective: The purpose of this study was to compare ultrasound and color Doppler features of thyroid nodules with ultrasound-guided FNAC results to determine the relative importance of these features in predicting the risk of malignancy. Methodology: This prospective cross-sectional study was conducted in Birat medical college teaching hospital in Tankisinuwari, Morang, Nepal. The study was conducted from September 2019 to April 2021. In total sixty-one patients with thyroid nodules were evaluated for sonographic characteristics. Finally, USG guided FNA for cytopathological examination was performed. Both descriptive and inferential statistics were used to analyze the result. Results: Out of the 61 patients, 34 (55.7%) were females and 27 (44.2%) were males. Majority of the malignant nodules were solid 11 (91.6%), whereas cystic and mixed nodules were predominantly seen in benign nodules 18 (36.7%) and 30 (61.2%) respectively. In malignant nodules 10 (83.3%) were heterogeneous and 2 (16.6%) were isoechoic. In benign nodules 29 (59.1%) were heterogeneous and 15 (30.6%) were anechoic with comet-tail artifact and 5 (10.2%) were isoechoic. Among 12 malignant cases, internal and peripheral vascularity were equally present in six cases each. Benign nodules showed peripheral vascularity in 48 (97.9%) and internal vascularity was noted in only one nodule. All of the malignant nodules showed calcification. None of the benign nodules showed micro-calcification. In malignant cases, cervical lymph nodes were present in 7 (58.3%) and absent in 5 (41.6%). In benign cases, cervical lymph nodes were present in 4 (8.1%) and absent in 45 (91.83%). Conclusion: The ultrasound features associated with malignancy in thyroid nodules are predominantly solid component, presence of micro-calcifications and internal vascularity. Enlarged cervical lymph nodes are good predictors for malignancy. USG guided FNAC confirms the suspicious features of thyroid nodules seen on USG.